REVIEW: PIERRE KLOSSOWSKI, LIVING CURRENCY - Calabrese, Nickolas (The Nordic Journal of Aesthetics, 2018)
Pierre Klossowski’s last major theoretical text Living Currency (2017) saw it’s first official1 translation into English in May 2017, nearly fifty years after it was published in French. On the back of the book is a blurb quoting Foucault, in which he calls it ‘the greatest book of our time’. This was almost certainly hyperbole; but whether or not his appraisal was correct (and I assure you it was not), it is a good book that advances a key to understanding Klossowski’s literary and visual relationship to the exploited and monetized body, as this is the preoccupying theme throughout his fictional, non-fictional, and visual art.